2017
DOI: 10.1108/ijhcqa-08-2016-0119
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies for guidelines at ICUs: a systematic review

Abstract: Purpose The purpose of this paper is to critically analyze empirical studies related to the implementation strategies for clinical practice guidelines (CPGs) in intensive care units (ICUs). Design/methodology/approach A systematic review with a narrative synthesis adapted from Popay et al.'s method for a narrative synthesis was conducted. A search using CINAHL, Google Scholar, Academic search complete, Cochrane Register for Randomized Controlled Trials, MEDLINE via PUBMED and grey literature was conducted in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Our search strategy yielded the following results: 925 hits, four studies selected: 2 systematic meta-reviews [ 24 , 25 ], 1 systematic review [ 26 ], 1 qualitative focus group study [ 27 ]. 190 hits, four studies selected: 3 randomized controlled trials [ 28 30 ], 1 retrospective cohort study [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search strategy yielded the following results: 925 hits, four studies selected: 2 systematic meta-reviews [ 24 , 25 ], 1 systematic review [ 26 ], 1 qualitative focus group study [ 27 ]. 190 hits, four studies selected: 3 randomized controlled trials [ 28 30 ], 1 retrospective cohort study [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…925 hits, four studies selected: 2 systematic meta-reviews [ 24 , 25 ], 1 systematic review [ 26 ], 1 qualitative focus group study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bemerkenswert ist der deutliche Wunsch nach Weiterbildung direkt am Arbeitsplatz. Eine maßgeschneidertes Implementierungskonzept [ 8 ] gilt bekanntermaßen als vorteilhaft und sollte im weiteren Verlauf evaluiert werden. Insbesondere Webinare als interaktive Plattform zur Vermittlung komplexer Inhalte und als Alternative zu Präsenzveranstaltungen aufgrund der Kontaktbeschränkungen stoßen bei der Mehrheit der Befragten auf Akzeptanz und wurden zuvor schon als effektives Mittel der Evidenzvermittlung in der Pandemie beschrieben [ 9 ].…”
Section: Diskussionunclassified
“…The multicomponent programs were associated with decreased pressure injury incidence in critically ill patients. A review of strategies used in implementing clinical practice guides in ICU suggested that multi-faceted interventions such as care bundles were more effective than single component interventions (Jordan et al, 2017). However, a recent systematic review found that research evidence on the effectiveness of care bundles were mostly of low quality (Lavallee et al, 2017).…”
Section: Programs and Their Componentsmentioning
confidence: 99%
“…The benefits of new roles or clarified roles can be three-fold. Firstly, staff in these roles can be champions, which has been found to be an effective strategy to enhance CPG implementation in ICU (Jordan et al, 2017) and to lead and reinforce research evidence uptake and improve compliance to protocols (Miech et al, 2018). Secondly, this helps to build capacity in promoting evidence-based practice.…”
Section: Implementation Strategiesmentioning
confidence: 99%